A defect-free thin film nanocomposite film and its preparation method and application
By tannin modification of layered dihydroxide and reacting with polyamide matrix to build a bridge structure, the trade-off problem of TFC membranes between flux and retention is solved, the permeability and retention of the membrane are improved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202411447840.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing TFC reverse osmosis membranes are difficult to weigh between flux and retention, while leakage and aggregation of nano-scale particles lead to degradation of membrane performance, and the functionalization process is complex and costly.
Tannic acid (TA) is used to modify the layered dihydroxide (LDH) and react with m-phenylenediamine (MPD) and trimethylol chloride (TMC) to construct a bridge structure between LDH and polyamide matrix to enhance the compatibility of nanomaterials and polyamide matrix.
Effectively prevent nanoparticles from leaking, improve the water permeability and retention of the membrane, reduce the risk of reduced membrane selectivity, and simplify the preparation process and reduce costs.
Smart Images

Figure CN118949705B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane treatment, in particular to a defect-free thin film nano composite material membrane and a preparation method and application thereof. Background Art
[0002] Given the importance of clean water supply to human welfare and economic development, research on water supply based on membrane technology is booming. After decades of efforts, reverse osmosis has become the mainstream technology for global freshwater supply and water purification due to its simple process and excellent energy efficiency. Currently, thin film composite (TFC) membranes are formed by interfacial polymerization on a porous polymer substrate, in which amine monomers in aqueous solution diffuse into the organic phase and react violently with acyl chlorides at the water / oil interface. It is characterized by excellent water permeability, salt rejection, and good tolerance to pressure and pH changes. Although the TFC-based reverse osmosis process has matured, its research progress still attracts global attention due to the widespread use of TFC reverse osmosis membranes in many desalination applications.
[0003] Recently, the rapid development of porous nanomaterials has promoted the research of thin film nanocomposite (TFN) membranes. Nanomaterials are becoming promising fillers in the selective layer due to their high porosity and specific surface area, controllable and well-defined pore size, multifunctional surface chemistry and good compatibility with polymer materials. With the help of well-designed nanomaterials, TFN membranes are expected to overcome the "flux-rejection" trade-off of traditional TFC membranes. However, the high cost of synthetic nanomaterials and the complex manufacturing procedures limit their practical application. Therefore, we should consider low-cost nanomaterials that are easy to prepare and compatible with existing membrane manufacturing processes. Layered double hydroxides (LDHs) are a class of synthetic nanoclays composed of two-dimensional layers of positively charged hydroxides and exchangeable charge-balancing anions. They have the advantages of low cost, simple preparation and good stability. The layered structure of LDHs exhibits molecular sieving behavior and provides additional channels for water molecules. In addition, LDHs can be further surface modified for different applications. By carefully selecting cations and intercalating anions, LDHs with flexible chemical compositions and tunable interlayer spacing can be obtained, making them effective nanofillers in TFN membranes.
[0004] Several challenges need to be overcome before the new TFN membrane can be successfully industrialized. One of the technical difficulties is how to effectively prevent these nanoparticles from leaking from the membrane into the permeate, which not only leads to a decrease in membrane performance, but also poses a potential threat to environmental safety and human health. In addition, during the membrane manufacturing process, the aggregation of nanoparticles is often difficult to avoid. Although this phenomenon can improve permeability, it will weaken the selectivity of the membrane. Therefore, it is necessary to build a strong chemical bond between the nanoparticles and the polyamide matrix. To solve these problems, many studies have been devoted to functionalizing nanomaterials. For example, Zheng et al. synthesized sulfonated multi-walled carbon nanotubes with alkyl sulfonic acid groups, which made the resulting TFN membrane show higher surface hydrophilicity and water flux (Journal of Membrane Science (2017), 524, 344-353). However, it is worth noting that the functionalization process of nanomaterials is usually accompanied by toxicity, labor-intensiveness, time-consuming and high cost, which limits the further development of related TFN membranes. To this end, it is urgent to develop a new method for preparing TFN membranes. Summary of the invention
[0005] In order to break the trade-off between "flux-rejection rate" of the existing TFC reverse osmosis membrane, the present invention provides a green, easy-to-prepare and scalable defect-free thin film nanocomposite membrane. The present invention uses an environmentally friendly modifier, tannic acid (TA), to modify LDH. TA can react with LDH, metaphenylenediamine (MPD) and trimesoyl chloride (TMC) at the same time, thereby playing a bridging role between LDH and the polyamide matrix. As a polyphenol widely present in plants, TA is first grafted onto LDH through electrostatic action. During the interfacial polymerization process, TA can react with the amino group on MPD through Michael addition or Schiff base reaction, or react with the acyl chloride group of TMC to generate an ester group. During the chemical cross-linking process with TMC, when the TA monomer is excessive, the unreacted terminal phenolic hydroxyl group or acyl chloride group will generate intermolecular gaps, thereby increasing the water molecule channel in the TFN membrane. In addition, due to the introduction of a large number of phenol groups, the application of TA gives the membrane surface more excellent hydrophilicity. The present invention successfully promotes the compatibility of nanomaterials and polyamide matrices at the molecular level, providing an effective strategy for manufacturing defect-free TFN membranes with high water permeability and high rejection rate.
[0006] The first object of the present invention is to provide a method for preparing a defect-free thin film nanocomposite film, comprising the following steps:
[0007] Provide a mixed aqueous solution containing sodium dodecyl sulfate (SDS) and metaphenylenediamine (MPD), and trimesoyl chloride solution (TMC);
[0008] Layered double hydroxide-tannic acid particles are prepared by using layered double hydroxide dispersion (LDH) and tannic acid solution (TA);
[0009] The layered double hydroxide-tannic acid particle dispersion liquid and trimesoyl chloride solution (TMC) are stirred and mixed to obtain the layered double hydroxide-tannic acid particle dispersion liquid;
[0010] The substrate film is immersed in a mixed aqueous solution containing sodium dodecyl sulfate and m-phenylenediamine for 2 to 5 minutes, the layered double hydroxide-tannic acid particle dispersion is directly poured on the surface of the substrate film to allow it to contact for 40 to 60 seconds, and then heat treated for 4 to 8 minutes to obtain the defect-free thin film nanocomposite film TFN film, which is placed in air for cooling for 5 to 8 minutes and immersed in ethanol for 2 to 5 minutes.
[0011] In some embodiments of the present invention, the layered double hydroxide dispersion is prepared by the following method:
[0012] Step S1: Preparation of Mg 2+ With Al 3+ Aqueous solution of
[0013] Step S2: adding equal volumes of Na2CO3 aqueous solution and NaOH aqueous solution to the solution in step S1 until the pH value reaches about 10;
[0014] Step S3: centrifuging the solution in step S2 to separate the LDH particles, and washing them twice with water and acetone respectively;
[0015] Step S4: re-dispersing the LDH particles obtained in step S3 in an organic solvent to obtain an LDH-ethanol dispersion;
[0016] Mg in the aqueous solution of step S1 2+ With Al 3+ The molar concentration ratio is 2:1~3:1.
[0017] Mg 2+ Selected from Mg(NO3)2, MgCl2, Mg(CH3COO)2, MgSO4.
[0018] Al 3+ Selected from Al(NO3)3, AlCl3, Al2(SO4)3.
[0019] The molar concentration ratio of Na2CO3 aqueous solution to NaOH aqueous solution is 1:3~1:5.
[0020] In some embodiments of the present invention, the concentration of sodium dodecyl sulfate in the mixed aqueous solution is 0.15-0.2 wt %, and the concentration of m-phenylenediamine in the mixed aqueous solution is 1-2 wt %.
[0021] In some embodiments of the present invention, the concentration of the trimesoyl chloride solution is 0.15-0.2 wt %.
[0022] In some embodiments of the present invention, the mass ratio of the layered double hydroxide in the layered double hydroxide dispersion to the tannic acid in the tannic acid solution is 10:1 to 5:1.
[0023] In some embodiments of the present invention, the concentration of the layered double hydroxide dispersion is 0.5-2 wt %,
[0024] The cation of the layered double hydroxide in the layered double hydroxide dispersion is selected from Mg 2+ 、Al 3+ , Ca 2+ 、Co 2+ 、Ni 2+ , Mn 2+ , Cu 2+ 、Zn 2+ , Fe 3+ Cr 3+ Any two of; preferably Mg 2+ 、Al 3+ Double hydroxide.
[0025] The solvent of the layered double hydroxide dispersion is ethanol, isopropanol or acetone.
[0026] In some embodiments of the present invention, the concentration of the layered double hydroxide-tannic acid particles in the layered double hydroxide-tannic acid particle dispersion is 0.1-0.2 wt %.
[0027] In some embodiments of the present invention, the substrate membrane is selected from polysulfone, polyethersulfone, and polyvinylidene fluoride membrane.
[0028] The immersion time is 2 to 5 min;
[0029] The time of direct contact with the basement membrane surface is 40 to 60 seconds;
[0030] The heat treatment time is 4 to 8 min;
[0031] The cooling time is 5 to 8 min;
[0032] The soaking time is 2 to 5 min.
[0033] The second object of the present invention is to provide a defect-free thin film nanocomposite film obtained by the above preparation method.
[0034] The third object of the present invention is to provide the use of the defect-free thin film nanocomposite membrane in separating NaCl from a salt water solution.
[0035] The above technical solution of the present invention has the following advantages compared with the prior art:
[0036] (1) By modifying LDH with TA, the present invention successfully constructs a bridging structure between LDH and the polyamide matrix through the interaction between TA and LDH, MPD and TMC, thereby effectively preventing the environmental risks caused by the leakage of nanoparticles from the membrane into the permeate and preventing the reduction of membrane selectivity due to the aggregation of nanoparticles.
[0037] (2) TA can react with the acyl chloride of TMC to generate ester groups. During the chemical cross-linking process of TA and TMC, when the TA monomer is in excess, the unreacted terminal hydroxyl or acyl chloride groups will generate intermolecular gaps, thereby increasing the water molecule channels in the TFN membrane and significantly improving the permeation flux.
[0038] (3) Since a large number of phenol groups are introduced into the defect-free film of the present invention, the application of TA makes the membrane surface exhibit more superior hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0040] Figure 1 It is a schematic diagram of the preparation method of the TFN film obtained in Examples 1-3 of the present invention.
[0041] Figure 2 1 is a scanning electron microscope image of the TFN membrane obtained in Example 2 of the present invention and the TFC membrane obtained in the comparative example.
[0042] Figure 3 The water permeability and desalination performance of the TFN membrane obtained in Example 2 of the present invention and the TFC membrane obtained in the comparative example are shown. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0044] Example 1
[0045] The method for preparing defect-free TFN film based on LDH-TA includes the following steps, and the flow chart is shown in Figure 1 :
[0046] (1) Synthesis of LDH: First, prepare 100 mL of an aqueous solution containing 0.2 M Mg(NO3)2 and 0.1 M Al(NO3)3. Then, add equal volumes of 0.2 M Na2CO3 aqueous solution and 1 M NaOH aqueous solution to the solution until the pH value reaches about 10. Next, separate the LDH particles by centrifugation, wash them twice with water and acetone, and finally redisperse them in ethanol to obtain an LDH particle dispersion with a concentration of 1 wt%.
[0047] (2) Synthesis of LDH-TA: 0.025 g of TA was dissolved in 1 mL of ethanol, and then mixed with 25 g of the LDH particle dispersion obtained in step (1) and vortexed for 2 min. After that, the LDH-TA particles were extracted by centrifugation and washed with water and acetone. Subsequently, the LDH-TA particles were dried at 80 °C for 24 h, ground and sieved (60 mesh, 0.3 mm).
[0048] (3) Preparation of TFN membrane: First, the PSF substrate was immersed in a 2 wt% MPD aqueous solution containing 0.15 wt% SDS for 2 minutes. Then, the residual solution was gently removed with a rubber roller. Subsequently, the PSF substrate soaked in MPD was mounted on a plastic frame. At the same time, LDH-TA particles were added to a n-hexane solution containing TMC and stirred for 45 minutes; then, a n-hexane solution containing 0.15 wt% TMC and 0.1 wt% LDH-TA was directly poured on the surface of the PSF substrate soaked in MPD and allowed to contact for 1 minute to obtain a TFC membrane. The obtained TFN membrane was heat treated at 80 °C for 4 minutes, then cooled in air for 5 minutes, and then immersed in ethanol for 5 minutes to obtain a defect-free TFN membrane.
[0049] Example 2
[0050] The method for preparing defect-free TFN film based on LDH-TA includes the following steps, and the flow chart is shown in Figure 1 :
[0051] (1) Synthesis of LDH: First, prepare 100 mL of an aqueous solution containing 0.2 M Mg(NO3)2 and 0.1 M Al(NO3)3. Then, add equal volumes of 0.2 M Na2CO3 aqueous solution and 1 M NaOH aqueous solution to the solution until the pH value reaches about 10. Next, separate the LDH particles by centrifugation, wash them twice with water and acetone, and finally redisperse them in ethanol to obtain an LDH particle dispersion with a concentration of 1 wt%.
[0052] (2) Synthesis of LDH-TA: 0.025 g of TA was dissolved in 1 mL of ethanol, and then mixed with 25 g of the LDH particle dispersion obtained in step (1) and vortexed for 2 min. After that, the LDH-TA particles were extracted by centrifugation and washed with water and acetone. Subsequently, the LDH-TA particles were dried at 80 °C for 24 h, ground and sieved (60 mesh, 0.3 mm).
[0053] (3) Preparation of TFN membrane: First, the PSf substrate was immersed in a 2 wt% MPD aqueous solution containing 0.15 wt% SDS for 2 minutes. Then, the residual solution was gently removed with a rubber roller. Subsequently, the PSF substrate soaked in MPD was mounted on a plastic frame. At the same time, LDH-TA particles were added to a n-hexane solution containing TMC and stirred for 45 minutes; then, a n-hexane solution containing 0.15 wt% TMC and 0.15 wt% LDH-TA was directly poured on the surface of the PSF substrate soaked in MPD and allowed to contact for 1 minute to obtain a TFC membrane. The obtained TFN membrane was heat treated at 80 °C for 4 minutes, then cooled in air for 5 minutes, and then immersed in ethanol for 5 minutes to obtain a defect-free TFN membrane. The obtained TFN membrane was structurally characterized, see Figure 2 .
[0054] Example 3
[0055] The method for preparing defect-free TFN film based on LDH-TA includes the following steps, and the flow chart is shown in Figure 1 :
[0056] (1) Synthesis of LDH: First, 100 mL of an aqueous solution containing 0.2 M Mg(NO3)2 and 0.1 M Al(NO3)3 was prepared. Then, equal volumes of 0.2 M Na2CO3 aqueous solution and 1 M NaOH aqueous solution were added dropwise to the solution until the pH value reached about 10. Next, the LDH particles were separated by centrifugation, washed twice with water and acetone, and finally redispersed in ethanol with a final concentration of 1 wt%.
[0057] (2) Synthesis of LDH-TA: 0.025 g of TA was dissolved in 1 mL of ethanol, and then mixed with 25 g of the LDH particle dispersion obtained in step (1) and vortexed for 2 min. After that, the LDH-TA particles were extracted by centrifugation and washed with water and acetone. Subsequently, the LDH-TA particles were dried at 80 °C for 24 h, ground and sieved (60 mesh, 0.3 mm).
[0058] (3) Preparation of TFN membrane: First, the PSf substrate was immersed in a 2 wt% MPD aqueous solution containing 0.15 wt% SDS for 2 minutes. Then, the residual solution was gently removed with a rubber roller. Subsequently, the MPD-soaked PSF substrate was mounted on a plastic frame. At the same time, LDH-TA particles were added to a hexane solution containing TMC and stirred for 45 minutes. Then, a hexane solution containing 0.15 wt% TMC and 0.2 wt% LDH-TA was directly poured on the surface of the MPD-soaked PSF substrate to contact it for 1 minute to obtain a TFC membrane. The obtained TFN membrane was heat treated at 80 °C for 4 minutes, then cooled in air for 5 minutes, and then immersed in ethanol for 5 minutes to obtain a defect-free TFN membrane.
[0059] Comparative Example 1
[0060] The method for preparing the TFC membrane comprises the following steps:
[0061] First, the PSF substrate was immersed in a 2 wt% MPD aqueous solution containing 0.15 wt% SDS for 2 minutes. Then, the residual solution was gently removed with a rubber roller. Subsequently, the PSF substrate soaked in MPD was mounted on a plastic frame, and a n-hexane solution containing 0.15 wt% TMC was poured directly on the surface of the PSF substrate soaked in MPD to allow it to contact for 1 minute to obtain a TFC membrane. The obtained TFC membrane was heat treated at 80 °C for 4 minutes, then cooled in air for 5 minutes, and then immersed in ethanol for 5 minutes to obtain a TFC membrane. The obtained membrane was structurally characterized, and the results are shown in Figure 2. Figure 2 .
[0062] Performance Testing and Characterization
[0063] To evaluate the separation performance of the membrane, a cross-flow reverse osmosis system with an operating area of 15 cm 2 , the feed flow rate was 1 L / min. The water permeability (LMH / bar) and salt rejection (%) were measured at 20 ± 1 bar, with 2000 ppm NaCl in the feed liquid. A circulating cooler was used to maintain the feed temperature at 25 ± 1 °C throughout the test. The experimental results are shown in Figure 3 .
[0064] Figure 2The surface and cross-sectional morphologies of the TFN membrane obtained in Example 2 and the TFC membrane obtained in Comparative Example 1 are shown. As can be seen from the surface images, both the TFC and TFN membranes present a polyamide layer with a leaf-like structure, indicating that the addition of LDH-TA nanoparticles has no significant effect on the polyamide network. In addition, the presence of LDH-TA nanoparticles can be observed in the polyamide matrix (red circle), further verifying the successful embedding of LDH-TA nanoparticles in the selective layer.
[0065] Figure 3 The water permeability and desalination performance of the TFN membranes obtained in Examples 1-3 and the TFC membrane obtained in Comparative Example 1 are shown. It can be observed from the figure that with the increase of the LDH-TA particle loading, the water permeability gradually increased from 2.40 LMH / bar to 3.45 LMH / bar, an increase of 43.75%. This shows that with the assistance of LDH-TA particles, the water permeability of the membrane is significantly improved, while the desalination performance does not show a significant decrease, maintaining a high desalination rate of more than 98.5%.
[0066] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a defect-free thin film nanocomposite film, characterized in that: The following steps are involved: Provide a mixed aqueous solution containing sodium dodecyl sulfate and m-phenylenediamine, and a trimesoyl chloride solution; Layered double hydroxide-tannic acid particles are prepared by using a layered double hydroxide dispersion and a tannic acid solution; The layered double hydroxide-tannic acid particles are stirred and mixed with the trimesoyl chloride solution to obtain a layered double hydroxide-tannic acid particle dispersion; The substrate film is immersed in a mixed aqueous solution containing sodium dodecyl sulfate and m-phenylenediamine, the layered double hydroxide-tannic acid particle dispersion is directly contacted with the surface of the substrate film, and then heat-treated to obtain the defect-free thin film nanocomposite film; The concentration of sodium dodecyl sulfate in the mixed aqueous solution is 0.15-0.2 wt %, and the concentration of m-phenylenediamine in the mixed aqueous solution is 1-2 wt %; The concentration of the trimesoyl chloride solution is 0.15-0.2 wt %; The concentration of the layered double hydroxide-tannic acid particles in the layered double hydroxide-tannic acid particle dispersion is 0.1-0.2 wt %.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the layered double hydroxide in the layered double hydroxide dispersion to the tannic acid in the tannic acid solution is 10:1-5:
1.
3. The preparation method according to claim 1, characterized in that: The concentration of the layered double hydroxide dispersion is 0.5-2 wt %; The solvent of the layered double hydroxide dispersion is ethanol, isopropanol or acetone.
4. The preparation method according to claim 1, characterized in that: The cation of the layered double hydroxide in the layered double hydroxide dispersion is selected from Mg 2+ 、Al 3+ , Ca 2+ 、Co 2+ 、Ni 2+ , Mn 2+ , Cu 2+ 、Zn 2+ , Fe 3+ Cr 3+ Any two of .
5. The preparation method according to claim 1, characterized in that: The basement membrane is selected from polysulfone, polyethersulfone, and polyvinylidene fluoride membrane; The immersion time is 2 to 5 min; The time of direct contact with the basement membrane surface is 40 to 60 seconds; The heat treatment time is 4 to 8 minutes.
6. A defect-free thin film nanocomposite film obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the defect-free thin film nanocomposite membrane according to claim 6 in separating NaCl from a saline solution.
Citation Information
Patent Citations
Modification of layered double hydroxides
CN104125928A
Metal organic framework composite intermediate layer forward osmosis membrane and preparation method thereof
CN116672899A